Inhibition of membrane complement inhibitor expression (CD46, CD55, CD59) by siRNA sensitizes tumor cells to complement attack in vitro - Geis, Nicolas; Zell, Stefanie; Rutz, Renate; Li, Wenhan; Giese, Thomas; Mamidi, Srinivas; Schultz, Stefan; Kirschfink, Michael (Current cancer drug targets, 2010)
The efficacy of cancer-immunotherapy with complement-activating monoclonal antibodies is limited by over-expression of one or more membrane-bound complement regulatory proteins (mCRPs: CD46, CD55, CD59) on the surface of neoplastic cells. In this study we designed small interfering RNAs (siRNAs) for posttranscriptional gene knock down of CD46, CD55 and CD59 aiming at to sensitize tumor cells to complement attack and thereby to better exploit complement for tumor cell destruction. Tumor cell lines of different origin, such as Du145 (prostate), BT474 (breast) and K562 (erythroleukemia) were selected for the study. FACS-analysis demonstrated that siRNA anti-CD46(301) reduced CD46 protein expression up to 80%, siRNA anti-CD55(255) diminished CD55 protein expression up to 49%, and CD59 protein expression was inhibited up to 82% by siRNA anti-CD59(1339). Time course experiments revealed a long-lasting silencing effect with >50% complement regulator inhibition up to day 13. Upon mCRP knock down, complement-dependent cytotoxicity (CDC) was augmented by 20-30% for CD46, by up to 24% for CD55 and by up to 55% for CD59. The combined inhibition of all three inhibitors further enhanced CDC by up to 66%. Dependent on the cell line, CD46 and CD55 downregulation increased significantly C3 ospsonization, which is known to support cell-mediated defense mechanisms. mCRP blocking antibodies were only partly able to further augment the tumor cells' susceptibility to complement lysis. Thus, siRNA-induced inhibition of complement regulator expression clearly sensitizes malignant cells to complement attack and, if specifically targeted to the tumor, appears suited as adjuvant to improve antibody-based cancer immunotherapy.